Cara Pandang Kaum Pentakostal Mencermati Pelayanan Petrus Sang Tokoh Kontraversi - Kosma Manurung (Sekolah Tinggi Teologi Real Batam, 2022)
For the Pentecostals, Peter's life was always interesting to observe. Peter, who was originally just a fisherman, usually fished, but his encounter with God turned him into a fisher of men. In addition, there were various supernatural events that Peter saw and experienced in his life. One of the interesting events to study that occurred in Peter's ministry, is presented very nicely in Acts 9:32-43 which the researcher then makes the purpose of this article by framing it from the perspective of the Pentecostals. The use of the method of description and support from literature review is expected to provide a clear, accurate, and adequate picture of the story of Peter's life and ministry, an overview of the story of Peter's ministry in the passage of Acts 9:32-34, and the perspective of the Pentecostals regarding this story. For the Pentecostals this story of Peter's enrichment provides an example in leadership and ministry, a life filled with God's supernatural powers, the importance of doing good to others, and a mandatory choice to live in a community of believers.Keywords: spiritual community; Peter's ministry; Pentecostal TheologyÂ AbstrakBagi kaum Pentakostal, kehidupan Petrus selalu menarik untuk dicermati. Petrus yang awalnya hanya seorang nelayan yang biasanya menjala ikan, namun pertemuannya dengan Tuhan merubahnya menjadi penjala manusia. Selain itu, ada berbagai peristiwa supranatural yang Petrus lihat dan alami dalam hidupnya. Salah satu peristiwa menarik untuk dikaji yang terjadi dalam pelayanan Petrus, disuguhkan dengan sangat apik dalam Kisah Para Rasul 9:32-43 yang kemudian peneliti jadikan tujuan dalam artikel ini dengan membingkainya dari cara pandang kaum Pentakostal. Penggunaan metode deskripsi dan dukungan dari kajian literatur diharapkan bisa memberikan gambaran yang jelas, cermat, dan memadai terkait selayang pandang kisah hidup dan pelayanan Petrus, gambaran kisah pelayanan Petrus dalam perikop Kisah Para Rasul 9:32-34, dan cara pandang kaum Pentakostal terkait kisah ini. Bagi kaum Pentakostal kisah pelayaan Petrus ini memberikan keteladanan dalam kepemimpinan maupun pelayanan, adanya kehidupan yang dipenuhi kuasa supranatural Allah, pentingnya berbuat baik kepada sesama, dan pilihan wajib untuk hidup dalam komunitas orang percaya.Kata kunci: komunitas rohani; pelayanan Petrus; teologi pentakostal